ANALISIS KESALAHAN MORFOLOGI DALAM SURAT DINAS DI DINAS PENDIDIKAN KABUPATEN MAJENE, SULAWESI BARAT - Jerniati I.; Musayyedah Musayyedah; Ratnawati Ratnawati (TELAGA BAHASA, 2021)
The purpose of this study is to describe the use of the Indonesian language with a specific sequence of morphological errors in the official letter of the Majene Regency Education Office. This study uses structural linguistic theory with morphological error analysis. This brief research uses a descriptive-analytical method that explains what it is about research object data. The data comes from outgoing official documents archived by the administrative staff of the Dinas Pendidikan of Majene Regency.. The results showed that the frequency of morphological errors was most often found in the wrong choice of words (including non-standard words). The frequency of frequent errors in the construction of words formed by prefixes or confixes in one of the basic words. Word constructions with such prefixes are generally written separately from the basic words. On the contrary, writing a proposition, in general, is written a series. Then the frequency of errors that are being an inaccurate diction on the construction of the opening letter of the letter which generally begins with the word "pay attention".Keywords: morphological errors, official letters, Dinas Pendididikan  of Majene Regencykesalahan morfologis dalam surat dinas di Dinas Pendidikan Kabupaten Majene. Penelitian ini menggunakan teori linguistik struktural dengan analisis kesalahan morfologi. Penelitian  singkat ini menggunakan metode deskriptif analitis yang memaparkan apa adanya tentang data objek penelitian. Data berasal dari surat-surat dinas keluar yang diarsipkan oleh tenaga administrasi Dinas Pendidikan Kabupaten Majene. Hasil penelitian menunjukkan bahwa frekuensi kesalahan morfologis yang paling sering terdapat pada pilihan kata yang tidak tepat (termasuk kata yang tidak baku). Frekuensi kesalahan yang sering adalah konstruksi kata yang dibentuk oleh prefiks di- atau konfiks di-kan dengan salah satu kata dasar. Konstruksi kata dengan prefiks seperti itu  pada umumnya ditulis terpisah dari kata dasarnya. Sebaliknya,  penulisan preposisi di pada umumnya ditulis serangkai. Kemudian frekuensi kesalahan yang sedang adalah diksi yang tidak cermat pada konstruksi kalimat pembuka surat yang umumnya diawali dengan kata “memperhatikan”.Kata kunci: kesalahan morfologi, surat dinas, Dinas Pendidikan Kabupaten Majene